From the Editor - Madrigal, Dennis V. (Philippine Social Science Journal, 2025)
Welcome to the first issue of Volume 8 of the Philippine Social Science Journal. As we step into 2025, the academic landscape continues to reflect a world in flux—one where traditional structures in religion, education, and the workplace are being reshaped by migration, technology, and the evolving human search for meaning. This issue brings together nine diverse studies that, while distinct in their disciplines, collectively explore how individuals and institutions are adapting to these dynamic shifts. From the quiet therapy of companionship to the bustling corridors of multi-specialty clinics and international classrooms, this collection offers a panoramic view of resilience and innovation.